Busca por inibidores de catepsinas em plantas do cerrado paulista e avaliação da proteólise tumoral in vitro - Ramalho, Suelem Demuner (2015)
The aim of this work is search for cysteine proteases inhibitors using a bioactivity-guided assay. We have selected different plants for the initial screening. Among all evaluated extracts, the ones obtained from Myrcia lingua Berg. showed to be the most potent. Cathepsin B and L are cysteine proteases which play a role in the degradation of extracellular matrix and facilitate tumor progression. Among the obtained inhibitors, flavonoids were the most active against CTSB (IC50 values from 4.9 to 37.2 μM). On the other side, triterpenes were more potent against CTSL (IC50 values from 2.4 to 39.5 μM). The triterpenes showed competitive inhibition and the flavonoids showed uncompetitive inhibition. Aiming to explore enzyme inhibition on tumor cells, we report proteolysis assay using live cell 3D model that allows to localize and to quantify proteolysis in live triple negative breast cancer cells. The natural inhibitors isolated from plants were evaluated against proteases on cell lysate but did not demonstrate good inhibition and we decided to evaluate synthetic cathepsin B inhibitors. A dipeptide nitrile compound (JK_1) was synthesized and then complexed with ruthenium II (JK_2). Caged bioactive molecules that can be active upon irradiation became a strategy to reduce side effects in surrounding tissues and facilitate spatial control over cysteine protease activity. On pure enzyme activity assay JK_2 was less active under dark (IC50 3.4 μM) comparing with light irradiation (IC50 0.3 μM), corresponding to a ratio of 12:1. Proteolysis assay using live cell demonstrated the inhibition of DQ-collagen IV by reducing fluorescence. Thus, the outcomes of this study could contribute to identify new hits for the development of potential anticancer drugs, once live cell imaging proteolysis assay is useful for verifying the efficacy of cathepsin inhibitors prior to testing in in vivo models.